Tracing the economic valuation of Mount Merbabu National Park: Benefit transfer method - Luthfi Alif Dinar Choirunnisa; Arkanudin Rizki Permono; Dio Caisar Darma; Dodi Tirtana (Journal of Economics Research and Policy Studies, 2026)
Natural resource management problems occur because the value of environmental services is often ignored compared to economic commodities, thus increasing pressure and degradation on the National Park forest area. This study analyzes the economic valuation of Mount Merbabu National Park to determine its estimated Total Economic Value (TEV), comprising direct use value (timber, non-timber products, water consumption), indirect use value (soil and water conservation, carbon sequestration, flood prevention, water transportation, and biodiversity), and non use value (option and existence value) as a quantitative basis for sustainability planning. The novelty of this study lies in the first application of the benefit transfer method to Mount Merbabu National Park, transferring reference values from the Food and Agriculture Organization (2009) report on Indonesian Conservation Forests by adjusting for an average inflation rate of 5.28% over the 23 years (2002–2025) and scaling to the park’s specific area of 5,820.49 ha. The findings estimate the 2025 economic value of the park at 82,894.81 US$/ha. Notably, Use Value dominates this figure at 77,382.23 US$ / ha, driven primarily by water consumption (32,795.54 US$/ha) and flood prevention (16,383.93 US$/ha), highlighting the vital role of direct and indirect ecological functions for the surrounding community.